Local Wisdom Values of the Pulo Traditional Village Community in Environmental Management - Yani Sri Astuti; Revi Mainaki; Anita Eka Putri (Department of Geography Education, University of Jember, 2022)
Local wisdom is the lives values ​that enables people to live in harmony with other individual and their environment. An example of a place that still maintains this value is a traditional village. West Java has eight Traditional Villages, one of which is the Pulo, located in Garut Regency, where the environment is still very well preserved because the values ​​of local wisdom are applied in environmental management. This study aims to analyzes the values ​​of local wisdom related to environmental management in Pulo Traditional Village community. Data were collected through observation, interviews, literature studies and documentation, then were analyzed descriptively using a qualitative ethnomethodology approach. The results showed that the community retains the value of local wisdom in maintaining their relationship with the environment by 1) preserving the prohibitions in the form of pamali, 2) prohibiting livestock rearing that pollutes the environment, 3) using certain plants wisely, as well as limiting the number of buildings and their occupants,and 4) constructing buildings with eco-friendly architecture. Therefore, these values need to be maintained to serve as a model or example for society in general. Keywords : Value of local wisdom; environmental management Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License